2012
DOI: 10.1017/s0007114512002231
|View full text |Cite
|
Sign up to set email alerts
|

Gene–diet interactions on plasma lipid levels in the Inuit population

Abstract: The Inuit population is often described as being protected against CVD due to their traditional dietary patterns and their unique genetic background. The objective of the present study was to examine gene -diet interaction effects on plasma lipid levels in the Inuit population. Data from the Qanuippitaa Nunavik Health Survey (n 553) were analysed via regression models which included the following: genotypes for thirty-five known polymorphisms (SNP) from twenty genes related to lipid metabolism; dietary fat int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
37
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 41 publications
6
37
3
1
Order By: Relevance
“…Although there was no evidence that directly reported the association between rs709158 and the LDL-C level, Lu et al have reported that the SNP was associated with TC, which suggested a possible relationship between this SNP and LDL-C or HDL-C. Besides, another intronic SNP, rs10865710, included in this study has been reported to be associated with the LDL-C level that supported our findings (Rudkowska et al, 2013). What is presented above may give a provable view that mutants even in introns of PPAR genes could also affect the LDL-C level of humans.…”
Section: Discussionsupporting
confidence: 88%
“…Although there was no evidence that directly reported the association between rs709158 and the LDL-C level, Lu et al have reported that the SNP was associated with TC, which suggested a possible relationship between this SNP and LDL-C or HDL-C. Besides, another intronic SNP, rs10865710, included in this study has been reported to be associated with the LDL-C level that supported our findings (Rudkowska et al, 2013). What is presented above may give a provable view that mutants even in introns of PPAR genes could also affect the LDL-C level of humans.…”
Section: Discussionsupporting
confidence: 88%
“…In 553 Inuit people, Rudkowska et al (2013) found that the rs5128 C allele frequency was 56.05%; however, we found that the rs5128 C allele frequency was 36.31%. Bhanushali and Das (2010) found that rs5128 was associated with dyslipidemia from a study in the Indian population.…”
Section: Discussioncontrasting
confidence: 75%
“…In recent years, as the development of molecular biology and genetic engineering technologies has progressed, studies have demonstrated a close association between the ApoE gene polymorphism and serum lipid levels (Shin et al, 2014;Yin et al, 2014;Zhu et al, 2014). It has also been found that dietary factors had some impact on blood lipids, and that this effect could be modified by receptor lipoprotein metabolism (Petkeviciene et al, 2012;Rudkowska et al, 2013). Research data showed that the ApoE polymorphism had a highly significant impact on lipid concentrations (Petkeviciene et al, 2012;Rudkowska et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that dietary factors had some impact on blood lipids, and that this effect could be modified by receptor lipoprotein metabolism (Petkeviciene et al, 2012;Rudkowska et al, 2013). Research data showed that the ApoE polymorphism had a highly significant impact on lipid concentrations (Petkeviciene et al, 2012;Rudkowska et al, 2013). However, environmental factors, including living conditions, diet, and living habits, were also shown to affect blood lipid levels and cerebral infarction (CI) (Egert et al, 2012;Petkeviciene et al, 2012;Rudkowska et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation